ANALYSIS OF THE EFFECT OF COAL QUALITY ON STEAM PRESSURE PRODUCED BY BOILER ENGINES IN PT. SINAR MEADOW INTERNATIONAL INDONESIA - Marvel, Marchello; Lusiani, Rina; Ula, Shofiatul; Jannah, Miftahul; Nugraha, Kurnia; Bagaskara, Rafly Priyantama Ramadhan; Mursyidah, Himmatul; Abdullah, Syarif (Trends in Mechanical Engineering Research, 2024)
In general, coal fossil fuel reserves are the main load in the industry, especially in the use of boiler engines. Coal comprises carbon, hydrogen, oxygen, nitrogen, sulfur, and mineral compounds. A boiler engine is a machine that produces high-pressure water vapor by heating water through fuels such as coal. The water vapor can then be used for various purposes, such as heating oil in the oil manufacturing industry, especially PT. Meadow Rays. Steam is an effective and inexpensive medium for transferring heat to a process. Coal plays an important role in the operation of boiler engines because coal is one of the fuels that is often used in the heating process. The quality of the coal can affect the quality of the steam produced by the boiler engine. Suitable coal shape for boilers at PT. Meadow rays are generally solid or solid, such as chunks, fractional coal, or bituminous coal that has a large coal size that has a mesh size between 3.2 mm to 6.3 mm or about 1/8 to 1/4 inch. This is because the solid, dense form of coal has a higher density and lower porosity, so it can retain heat better and provide a smaller surface for the combustion process. Coal users must be provided to PT. Sinar Meadow must have a minimum calorie of 6300 kcal/kg, for the efficiency and safety of the boiler at PT. Meadow Rays. Therefore, paying attention to the coal quality used in boiler engines is important to produce high-quality and efficient steam.